All States Close but Red Districts Reopen: The Politics of In-Person Schooling During the COVID-19 Pandemic. (December 2021) - Grossmann, Matt; Reckhow, Sarah; Strunk, Katharine O.; Turner, Meg
How did political factors and public health affect state and local education decisions during the COVID-19 pandemic, especially the continuation of in-person schooling? Using an original data set of state policies, we find that governors ordered school closures in spring 2020 but left decisions to districts in the fall, regardless of partisanship. Analyzing local district reopening plans, however, we find that decisions were more tied to local political partisanship and union strength than to COVID-19 severity. Republicans in the public were also more favorable than Democrats toward in-person learning. States' decisions to leave reopening plans to their districts opened the way for the influence of local partisanship.